Korelasi Kuat Tekan Bebas (UCT) Dengan Kuat Geser Langsung (Direct Shear Test) Pada Tanah Lempung - Chriznawati Sari; Irwan Lie Keng Wong; Helen Adri Irene Sopacua (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
This study aims to determine the correlation of compressive streght and shear strength in clay varied with bottom ash mixture. The soil tested in this study came from Jl.Poros Malino-Makassar, RW 63 Paringgi, Kec. Tinggi moncong , Kab. Gowa, South Sulawesi. In the contruction of structuction on clay soil will cause several problems, such as the small value of the compressive strength and shear strength of the soil. In order to know the results. To see the behavior of this structure, bottom ash is mixed with bottom ash mixture variations.To find out the effect of combining clay soil with bottom ash on compressive strength and shear strength vales, it was done by combining bottom ash of 0%, 15%,20%,25%, and 30%. The test was carried out mechanically, namely direct shear strength and compressive strength testing to determine the correlation vetween the stress value (qu) and the direct shear value (Cu). From the results of this independent com[pressive strength test, the highest stress value (qu) was obtained at point 1 obtained at 30% variation of 0.278 (kg/cm2) and the direct shear strength lest obtained the highst direct shear value (Cu) at poin 1 obtaind at 30% variation of 0.111 (kg/cm2), at poin the 2 largest stress values (qu) are at 30% variation of 0.262 (kg/cm2) and the largest direct shear values (Cu) are at 30% variation of 0.103 (kg/cm2) . So it can be said that the value of the independent compressive strength test and the direct shear strength value are correlated with eact other because both have increased, the higher the bottom ash dose, the higjer the direct shear value (Cu) and the stress value (qu).